Promising Adsorption of Sulfidic Acid Gases Using Wet Banana Plant Adsorbent (Musa spp.) - Haryono Setiyo Huboyo; Badrus Zaman; Bimastyaji Surya Ramadan; Anastasia Dinda Prinaningrum (Institute for Research and Community Services, Institut Teknologi Bandung, 2022)
Bananas have the highest production rate among fruits in Indonesia, which leads to the generation of a significant amount of banana fruit solid waste. In this study, we assessed the potential use of banana waste to remove hydrogen sulfide (H2S) gas. In particular, the purpose of this study was to analyze the efficiency of banana waste as an adsorbent for H2S gas. We tested the stems, leaves, and peels of banana plants as H2S gas adsorbents with varying contact times. To obtain a microscopic view of the adsorbents before and after the experiment, we conducted measurements using scanning electron microscopy with dispersive X-ray spectroscopy. The banana leaves, stems, and peels were found to have H2S gas absorption efficiency values of 76.52%, 51.83%, and 6.44%, respectively. Based on the experiment, the leaves of the banana plant appear to be the best adsorbents, with an adsorption capacity of 1.67 mg/g. The results also revealed that there was a change in the fiber and stomata appearance of the banana leaves after the adsorption process. Overall, this research indicates that banana leaves have the potential to be used as effective H2S adsorbents.